TECHNICAL EFFICIENCY OF HORTICULTURAL FARMING IN CIANJUR DISTRICT - Rohayati Suci Indrianingsih; Eliana Wulandari; Tuti Karyani (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
Efficiency is important in horticultural farming, but farmers still do not understand how the concept is to achieve efficiency. This study aims to determine the factors of production that influence the production of horticulture in particular pakcoy and determine the efficiency level of pakcoy farming. The research design is quantitative with a survey method by distributing questionnaires. Questionnaires were distributed to 30 respondents who obtained by simple random sampling. The data were analyzed using multiple linear regression and stochastic frontier analysis. The research was conducted in Cipanas Sub-district, Cianjur District from August to November 2022. The results showed that the production factors related to the production of pakcoy were the use of ZA fertilizer and Score pesticide. ZA fertilizer and Score pesticide have a positive relationship with pakcoy production. Pakcoy farming in Cipanas Sub-district, Cianjur District can be identified as efficient. Efficiency in pakcoy cultivation in Cipanas District can still be improved to achieve maximum efficiency. Efficiency can be increased by adding the quantity of several production factors that are positively related to production, as well as reducing the use of production factors that have a negative relationship with production. Farmers can attend training on increasing technical efficiency so they can understand the concept of technical efficiency and apply it in their business.